Naive skepticism scale: development and validation tests applied to the chilean population - Rodrigo Ferrer-Urbina; Yasna Ramírez; Patricio Mena-Chamorro; Marcos Carmona-Halty; Geraldy Sepúlveda-Páez (Psicologia: Reflexão e Crítica, 2024)
Abstract Background Skepticism has traditionally been associated with critical thinking. However, philosophy has proposed a particular type of skepticism, termed naive skepticism, which may increase susceptibility to misinformation, especially when contrasting information from official sources. While some scales propose to measure skepticism, they are scarce and only measure specific topics; thus, new instruments are needed to assess this construct. Objective This study aimed to develop a scale to measure naive skepticism in the adult population. Method The study involved 446 individuals from the adult population. Subjects were randomly selected for either the pilot study (phase 2; n = 126) or the validity-testing study (phase 3; n = 320). Parallel analyses and exploratory structural equation modelling were conducted to assess the internal structure of the test. Scale reliability was estimated using Cronbach's alpha and McDonald's omega coefficients Finally, a multigroup confirmatory factor analysis was performed to assess invariance, and a Set- Exploratory Structural Equation Modeling was applied to estimate evidence of validity based on associations with other variables. Results The naive skepticism scale provided adequate levels of reliability (ω > 0.8), evidence of validity based on the internal structure of the test (CFI = 0.966; TLI = 0.951; RMSEA = 0.079), gender invariance, and a moderate inverse effect on attitudes towards COVID-19 vaccines. Conclusions The newly developed naive skepticism scale showed acceptable psychometric properties in an adult population, thus enabling the assessment of naive skepticism in similar demographics. This paper discusses the implications for the theoretical construct and possible limitations of the scale.